Representation of Muslimah in the Social Space in Downy Premium Perfume Advertisements - Khairul Syafuddin (2022)
Downy Premium Parfum is one of the advertisements that presents the figure of a Muslim woman. The advertise-ment presents Laudya Cynthia Bella as an actress who plays a muslim woman. This study uses representation theory to present the figure of Muslim women in social space. The purpose of this research is to determine the meaning formation process that occurs in Downy Premium Parfum advertisements in constructing the image of muslim women. This research uses a qualitative method with semiotic analysis techniques by Roland Barthes. The results of this study found that the Downy Premium Parfum advertisement tried to represent the fragrance through visual flowers. This flower sign is then attached to the actor to strengthen the image of Muslim women in the social space. In the end, the advertisement stated that women could appear on a par with men in the social space, namely the workspace.